The floral illusion: A parasitic beetle mimics the scent of flowers to attract bees - Ryan M. Alam; Danny Kessler; Heiko Vogel; Katrin Luck; Anja David; Maritta Kunert; Gunnar Brehm; Martin Kaltenpoth; Sarah E. O’Connor; Tobias G. Köllner (Proceedings of the National Academy of Sciences, 2026)
Animals are not known to biosynthesize floral chemical signals to manipulate pollinators, although such mimicry could profoundly shape plant–pollinator interactions. Larvae of the poisonous European blister beetle Meloe proscarabaeus parasitize multiple solitary bee species, yet the mechanism enabling host attraction has remained unresolved. Here we show that these larvae lure bees by emitting a bouquet of volatile compounds that closely resembles floral scent. Chemical analyses reveal a complex blend of monoterpenoids derived from ( S )-linalool, a ubiquitous floral volatile. Behavioral assays demonstrate that these compounds function as floral-scent mimics, eliciting attraction in bees and acting as allomones (i.e., interspecific chemical signals that benefit the emitter while disadvantaging the receiver). Transcriptomic and functional analyses identify cytochrome P450 enzymes that oxidize ( S )-linalool, suggesting that larvae biosynthesize these plant-like volatiles de novo. Together, these findings broaden the scope of interkingdom chemical mimicry and uncover a striking form of sensory deception in which an insect chemically assumes the signal identity of a flower, revealing that animals can evolve biosynthetic pathways to exploit plant–pollinator communication.